The children of Stanisław Antoni Szczuka buried in the crypt of the Holy Virgin Mary’s Church in Szczuczyn - Dudziński, Tomasz (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2016)
The article concerns the burials of the children of Stanisław Antoni Szczuka, a Crown Referendary and Lithuanian Chancellor, connected with kings John III Sobieski and Augustus II. The burials were identified during the archaeological explorations carried out between 2012 and 2014 in the crypts of the Holy Virgin Mary’s Church in Szczuczyn and belong to the adolescents: August Michał (1697–1702) and Maria Anna (1703–1705), as well as Marcin Leopold, who died at the age of 30 (1698–1728). The author confronts the preserved written sources with the material obtained through the archaeological investigation. Thanks to the source material, besides making the descriptions of the preserved coffins and remains of grave attire, it was also possible to reconstruct partially the burial ceremonies accompanying the funerals of Szczuka’s juvenile children
il. ; 24 cm
Keywords: Stanisław Antoni Szczuka; Konstancja Potocka; Szczuczyn; krypty; dzieci; 18 w.